VET teachers' learning in feminised vocations- a comparative study of Swedish floristry and hairdressing teachers. (2nd January 2020) - Gåfvels, Camilla
ABSTRACT: This article explores the continuing professional learning of Swedish hairdressing and floristry teachers, based on semi-structured interviews with six experienced female teachers. The research question that guided the work asks what continuing professional learning do experienced floristry and hairdressing teachers undertake in relation to their vocational field and to pedagogy. The analysis applies concepts from the theory of practice architectures, and focuses upon the sayings, doings and relatings that surface in the interview data. The findings indicate that the VET teachers handle their learning relatively independently of the schools at which they are employed. Furthermore, more personal agency was required from the floristry teachers, than from the hairdressing teachers for whom organised business interests provide ample education and training opportunities. The article argues that the VET teachers who rely on themselves and their colleagues can control their own continuing professional learning at their place of work.